Activated carbon from hydrolysis lignin: Effect of activation method on carbon properties. (April 2022) - Bergna, Davide; Varila, Toni; Romar, Henrik; Lassi, Ulla
Abstract: This study presents the effects of different activation methods to produce activated carbon from the hydrolysis lignin. Pretreatment of the feedstock with common mineral acids (HCL, HNO3, and H3 PO4 ), different steam rates for physical activation, and different chemical activating agents (ZnCl2, Na2 CO3, and KOH) for chemical activation were investigated. The pretreated biomass was carbonized and activated in one-stage process and the surface characteristics, such as total pore volume, pore size distribution and specific surface area, were investigated. The results showed that the activated carbon surface properties were not greatly affected by acid pretreatment. Brunauer-Emmett-Teller (BET) surface areas as high as 616 m 2 /g could be achieved with physical activation and 2054 m 2 /g with chemical activation. Different steam rates in the selected interval (0.5–2 cm 3 /min) did not change the pore size distribution but had small positive effect on the specific surface area, while chemical activation with ZnCl2 increased the mesoporosity, and activation with KOH increased the microporosity and oxygen groups in the form of ether and alcohol bonds. Highlights: Hydrolysis lignin as co-product from a Finnish biorefinery has been used as source material for activated carbon. Pretreatment with acid showed to not affect the final material. Physical activation with steam produces activated carbon with a stoichiometric relation between steam and material mass ratio independent on the rate. Chemical activation with ZnCl2, Na2 CO3 and KOH develops a consistent porous structure. Activation with KOH determines a functionalization on the carbon surface of oxygen groups in the shape of C–O.